Interactive Effects of meteorological Factors and Ambient air Pollutants on Mumps Incidences in Ningxia, China Between 2015 and 2019 - Liu, Weichen; Zhao, Shi; Gong, Rui; Zhang, Yajuan; Ding, Fan; Zhang, Lu; Li, Xiaolong; Wang, Ruonan; Ma, Ning; Zhao, Yu (Frontiers in Environmental Science, 2022)
Background: As a public health issue globally, existing evidence suggested that mumps epidemics are associated with meteorological factors and air pollutants at population scale. However, the interaction effect of meteorological factors and air pollutants on mumps remains under explored. Methods: Daily cases of mumps, meteorological factors and air pollutants were collected in Ningxia, China from 2015 to 2019. First, a distribution lag nonlinear model (DLNM) was employed to assess the confounding-adjusted relationship between meteorological factors, ambient air pollutants and mumps incidences. According to the results of DLNM, stratification in both air pollutants and meteorological factors were adopted to further explore the interaction effect of PM2.5 and O3 with temperature and relative humidity (RH). Results: We reported significant individual associations between mumps incidences and environmental factors, including temperature, relative humidity, PM2.5 and O3. Evident multiplicate and additive interactions between meteorological factors and PM2.5 were found with IRR of 1.17 (95%CI: 1.04, 1.33) and RERI of 0.21 (95%CI: 0.04, 0.37) for moderate level of temperature at 12.4°C, and IRR of 0.86 (95%CI: 0.76, 0.99), RERI of -0.14(95%CI: -0.26, -0.02) for high level of relative humidity at 58%, respectively. Regarding O3 and meteorological factors (temperature = 21°C), IRR and RERI were 1.34 (95%CI: 1.04, 1.72) and 0.26 (95%CI: 0.01, 0.50), respectively. Conclusions: Our findings indicated that meteorological factors and air pollutants imposed significantly lagged and nonlinear effect on the incidence of mumps. The interaction between temperature and PM2.5 as well as O3 appears synergistic, while relative humidity is antagonistic with PM2.5 but synergistic with O3. These results provide scientific evidence to relevant health authorities for the precise disease control and prevention of mumps in arid and semi-arid areas.